Comparative study of unilateral subcutaneous internal anal sphincterotomy and 02% diltiazem local application in acute fissure in ano: a study of 40 patients over 01 year - Varshney, Priyanshu M.; Ray, Mriganko S.; Nagyan, Tushar; Malhi, Sarvpreet S.; Thakore, Digpal H.; Modi, Naresh A.; Gupta, Sandhya (International Surgery Journal, 2021)
Background: Two most demoralizing things in life are physical pain and bad body odour. A counted few body pains are as terrible, as oppressive and as tormenting, almost on daily basis as the pain of fresh acute fissure in ano. It pins your whole being, your awareness of life and focus of living on to your painful anus. Anal fissures are commonly encountered in routine colorectal practice. Fissure has traditionally been treated surgically. Developments in the pharmacological understanding of the internal anal sphincter have resulted in more conservative approaches towards treatment. Methods: 40 patients with acute fissure in ano were divided into 02% diltiazem gel and unilateral subcutaneous internal anal sphincterotomy (USIAS) groups. Patients in the two groups were followed up subsequently. Results: Anal fissures were found completely healed in 14 (70%) out of 20 patients treated with 02% diltiazem gel between 4-8 weeks. Healing was 100% with “USIAS” group. The mean healing duration of fissure was 04.45 weeks in diltiazem gel group and 03.45 weeks in “USIAS” group. 65% patients were free from pain after treatment with diltiazem gel whereas 95% patients were free from pain after treatment with “USIAS”. Conclusions: This prospective study, demonstrates that “USIAS” is superior to pharmacological treatment of anal fissure with good symptomatic relief, high rate of healing with very low rate of complication. Patients who are not willing to undergo surgery may be managed by 02% diltiazem as pharmacological line of management for fissure in ano.